Measurement of the structure of potential cluster bands and absolute branching ratios of high-energy states in 18O*. (December 2020) - Pirrie, S.; Wheldon, C.; Kokalova, Tz.; Bishop, J.; Hertenberger, R.; Wirth, H.-F.; Bailey, S.; Curtis, N.; Dell'Aquila, D.; Faestermann, Th.; Mengoni, D.; Smith, R.; et al.
Abstract: The investigation of nuclei with potential α -cluster structure is of great importance to the understanding of nuclear structure, both in the testing of theoretical models and for the study of the synthesis of elements in stars. The 18 O nucleus is an excellent candidate to test for such a system, and an experiment has been performed in order to determine the validity of proposed cluster bands in 18 O, by measuring absolute branching ratios for high-energy excited states. In order to accurately measure these branching ratios, Monte-Carlo techniques have been employed allowing for the precision reproduction of data gathered throughout the experiment. An in-depth description of the considerations required when simulated data for these experiments and comparisons between features in real and simulated data are presented.